Vacant Land and Food Needs: How Do Students Utilize Both through the KRPL Concept, Is It Optimal? - Abdul Hamid; Sapto Hadi Riono; Anindita Verliana Ridho'i; Akhmad Kavin Abda; Shinta Dwi Ranti; Latipun (Jurnal Dedikasi, 2023)
The Graha Tartila settlement, Blandongan District, Pasuruan City, is experiencing rapid changes, especially agricultural land, which has been converted into residential areas and complexes. However, some land is empty, abandoned, and poorly maintained. In addition to its unkempt and dirty appearance, this abandoned land is also considered a nest for mosquito snakes and often becomes a garbage dump. This article aims to describe the use of empty land in Graha Tartila Housing, Blandongan District, Pasuruan City, as part of efforts to improve food security behavior in people's daily lives. The method used is experimental. People use empty land to grow daily food crops such as vegetables and Lombok. The trial results show that the use of empty land positively impacts the surrounding community, including maintaining environmental cleanliness and producing vegetables that can be consumed directly by the community. There is increased knowledge and training in preparing soil substrates, providing compost from local materials, and using waste and other materials as planting substrates. The approach to implementing a sustainable food space at home is carried out theoretically and practically. Applying KRPL is a solution to help small plots of land be optimal and effective.